Understanding the Molecular Crosstalk in Biological Processes - El-Esawi, Mohamed A. (IntechOpen, 2020)
It is essential to address the aspects related to the crosstalk approach in understanding complex biological processes in different organisms, including plants, microorganisms, animals, and humans. This will definitely provide the information required to achieve the biological advancements. Therefore, this book highlights the advances made in the research field covering crosstalk in different biological processes. Current research trends, future research directions, and challenges are also addressed. This book will provoke the interest of various readers, researchers, and scientists who will find this information useful for the advancement of their research on biological processes in living organisms.